Development of a Consensus-Based Cross-Domain Protocol for the Management of Elastic Compression Stocking Therapy in Patients With Deep Venous Thrombosis and Chronic Venous Disease: A Modified Delphi Study - Schreurs, Rachel H. P.; Joore, Manuela A.; ten Cate, Hugo; ten Cate-Hoek, Arina J. (Frontiers in Cardiovascular Medicine, 2022)
Objective: Elastic compression stocking (ECS) therapy is commonly used in patients with deep venous thrombosis (DVT) and chronic venous disease (CVD). The provision of ECS therapy is complex, and studies indicate a lack of practical guidance and suboptimal collaboration among health care professionals. We aimed to reach consensus on critical issues of ECS therapy among the involved health care professionals and patients. Methods: A three-round modified Delphi analysis was performed in the Netherlands in which 56 health care professionals (internists, dermatologists, general practitioners, emergency room nurses, home care nurses, medical stocking suppliers, and occupational therapists) and seven patients were invited. The 21 statements included in this analysis were based on information collected from a previously conducted Functional Resonance Analysis Method and Realist Evaluation. We used 7-point Likert scale questions and a 75% threshold for consensus. Results: Of the 63 persons invited for this study, 59 (94%) agreed to participate and responded in the first questionnaire round; of whom 52 were health care professionals and seven were patients (five DVT and two CVD). The overall response rate for the three questionnaire rounds was 91%. After completion of the rounds, full consensus was achieved on 19 out of 21 statements. No consensus was reached on the need for a follow-up appointment for CVD patients and who should be responsible to determine the ECS type (custom-made or standard). Conclusions: We identified 19 consensus-driven recommendations on treatment decisions and collaboration in ECS therapy among an interdisciplinary panel of health care professionals and patients. These recommendations form a basis for consensus-driven optimization of ECS therapy and should ideally be incorporated in a general cross-domain protocol for ECS therapy in patients with DVT and CVD.